(untitled) (Social Science Review, 2023)
This paper explains the relationship between economy and identity among the Oraons in Barind region of Northwest Bangladesh. Focusing on original in-depth ethnographic fieldwork in Barind, the paper concerns Oraons’ identity that how it is structured by their present economic condition as well as by the processes that have promoted internal Oraon diversity. Despite this concern, the paper depicts the processes of Oraons’ identity formation as minority group or adibashis or indigenous people. The Oraons, by claiming their identity rights as adibashis, strategically unite with other adibashi group from both Bangladesh and abroad, politically respond to global indigeneity. Theoretically, the paper thus contributes to the literature on ethnic studies explaining the relationship between economy and identity in the case of the Oraons. Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 39-57